2009
DOI: 10.5741/gems.45.3.158
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of "Green Amber" with Infrared and Nuclear Magnetic Resonance Spectroscopy

Abstract: Tucson gem shows in February 2008, where it was sold by amber dealers and distributors under names such as "natural green Caribbean amber" or "very rare Baltic amber" (Pedersen, 2008). This material, which has a peridot-like bright greenish yellow to green color, displays a distinctive deeper green component than previously seen in amber, even in the rare green material from Mexico. Author AA visited Treasure Green Amber Ltd. in June 2007 and was provided with information on the material by general manager Hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…Amber is heterogeneous in composition, but consists of a macromolecule formed by free radical polymerization of several precursors from the labdane family (e.g., communic acid, cummunol and biformene). 4,5 These labdanes are diterpenes and trienes, equipping the organic skeleton with three alkene groups for polymerization. Amber also contains succinoabietic acid.…”
Section: Compositionmentioning
confidence: 99%
“…Amber is heterogeneous in composition, but consists of a macromolecule formed by free radical polymerization of several precursors from the labdane family (e.g., communic acid, cummunol and biformene). 4,5 These labdanes are diterpenes and trienes, equipping the organic skeleton with three alkene groups for polymerization. Amber also contains succinoabietic acid.…”
Section: Compositionmentioning
confidence: 99%
“…The presence of a small absorption around 820 cm −1 in the FTIR spectra confirmed the use of multiple treatments on all the commercial "green amber" samples tested by Abduriyim et al (2009). Although the use of heat treatment on a specific piece can be ascertained, whether or not the original starting material was copal or amber still cannot be routinely identified.…”
Section: Hpht Treatment To Produce Colormentioning
confidence: 97%
“…Multiple treatments may increase the color saturation, producing an intense, pure green hue that has not been seen in untreated amber. The treatment also reportedly hardens the amber, making it more stable (Abduriyim et al, 2009). While infrared spectroscopy can distinguish amber from copal (Guiliano et al, 2007), this new treatment process "ages" the copal, rendering its properties similar to those of amber and making its identification as copal extremely difficult, even with advanced analytical methods.…”
Section: Hpht Treatment To Produce Colormentioning
confidence: 99%
“…e spectroscopic results indicate that over geological time, the unsaturated bonds are broken and gradually polymerized into a chain structure. Abduriyim et al [24] and Wang et al [14] concluded that during the conversion from resin to amber, the basic constituent labdanoid diterpenes are crosslinked to form a three-dimensional polymer chain structure. Lambert et al [9] presented a simplified scheme for the formation of amber ( Figure 5).…”
Section: Spectral Characteristics Indicate the Structures Of Rosinmentioning
confidence: 99%